OPTIMASI PEMILIHAN QUALITY ASSURANCE CV FORTUNE CLEAN MENGGUNAKAN METODE TOPSIS - Annisa Putri Gita Cahyani; Naurah Huwaida; Gandung Triyono (Jurnal Sistem Informasi dan Informatika (Simika), 2026)
CV Fortune Clean, a company providing cleaning services and products, requires Quality Assurance (QA) professionals to ensure the optimal performance of technological and system updates in its internal applications, which are vital for business processes such as inventory management and service scheduling. The previous recruitment process, reliant on manual CV screening and subjective interviews, took up to four months to identify truly competent candidates, causing delays in application updates and potentially hindering operational efficiency. To address this issue, this study designs a Decision Support System (DSS) based on the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. TOPSIS was chosen for its ability to evaluate candidates based on their proximity to an ideal solution, considering technical criteria and non-technical criteria (e.g., problem-solving and communication skills). The DSS implementation reduced recruitment time from four months to one month, enhanced selection accuracy by minimizing subjective bias, and proved more consistent than manual methods in comparative simulations. The TOPSIS system also improved transparency and objectivity in the selection process, optimizing recruitment duration and enhancing the quality of QA personnel to support the reliability of internal applications critical to business operations.